Euthanasia: Promoter of Autonomy or Supporter of Biopower? - Tsiakiri, Lydia (Conatus - Journal of Philosophy, 2022)
The medical developments and their subsequent influence on the duration of human life have brought in the limelight various moral questions. The pathological conditions do not constitute anymore the decisive causes of death, whereas an ascending number of people suffer more by being maintained in life. In this reality, the euthanasia debate seems more apropos than ever. The following article examines the aforementioned issue through the supportive argument of autonomy in contrast to a Foucauldian approach. In essence, based on the Kantian concept of autonomy, several scholars have advocated in favor of the legalization of euthanasia in order that our ability to define not only the course of our life and its duration, but also the way of our death is ensured. However, on the other side, a Foucauldian approach of the issue seems to be equally worth cited and taken into consideration. In accordance with that, the domination of Foucault’s concept of biopower would deterministically imply that our choices are totally determined by a form of power that targets at the absolute control over our lives through medicine and legislation. In such a context, euthanasia could not constitute a promoter of autonomy. On the contrary, it would contribute to the absolute escalation of the governmental power that would be imposed on every inch of our lives being exclusively interested in its own prosperity!